Interference effects in the Aharonov-Bohm geometries with Majorana bound states. (January 2018) - Zhang, Ya-Jing; Zhang, Shuai; Yi, Guang-Yu; Jiang, Cui; Gong, Wei-Jiang
Abstract: We investigate the transport properties in an Aharonov-Bohm circuit with embedded Majorana bound states (MBSs), by considering the influence of MBS-lead coupling manners. It is found that the inter-arm quantum interference plays an important role in modulating the Andreev reflection process. This is manifested as the fact that both the conductance and Fano factor are tightly related to the circuit geometry and the local magnetic flux. The results in this work can be helpful in describing the transport characteristics of the junction with MBSs. Highlights: We investigate the transport properties in an AB circuit with embedded MBSs. Influence of MBS-lead coupling manners is considered. Inter-arm quantum interference can efficiently modulate the Andreev reflection processes. The conductance and Fano factor are related to the circuit geometry and the magnetic flux. This work can be helpful in describing the transport property of the junction with MBSs.